Humanized monoacylglycerol acyltransferase 2 mice develop metabolic dysfunction-associated steatohepatitis - J. Jose Corbalan; Pranavi Jagadeesan; Karla K. Frietze; Rulaiha Taylor; Grace L. Gao; Grant Gallagher; Joseph T. Nickels, Jr. (Journal of Lipid Research)
Mice lacking monoacylglycerol acyltransferase 2 (mMGAT21) are resistant to diet-induced fatty liver, suggesting hMOGAT2 inhibition is a viable option for treating metabolic dysfunction-associated steatotic liver disease (MASLD)/metabolic dysfunction-associated steatohepatitis (MASH). We generated humanized hMOGAT2 mice (HuMgat2) for use in pre-clinical studies testing the efficacy of hMOGAT2 inhibitors for treating MASLD/MASH. HuMgat2 mice developed MASH when fed a steatotic diet. Computer-aided histology revealed the presence of hepatocyte cell ballooning, immune cell infiltration, and fibrosis. Hepatocytes accumulated Mallory-Denk bodies containing phosphorylated p62/sequestosome-1-ubiquitinated protein aggregates likely caused by defects in autophagy. Metainflammation and apoptotic cell death were seen in the livers of HuMgat2 mice. Treating HuMgat2 mice with elafibranor reduced several MASH phenotypes. RNASeq analysis predicted changes in bile acid transporter expression that correlated with altered bile acid metabolism indicative of cholestasis. Our results suggest that HuMgat2 mice will serve as a pre-clinical model for testing hMOGAT2 inhibitor efficacy and toxicity and allow for the study of hMOGAT2 in the context of MASH.